2017
DOI: 10.1128/jvi.02049-16
|View full text |Cite
|
Sign up to set email alerts
|

The Human Cytomegalovirus IE1 Protein Antagonizes PML Nuclear Body-Mediated Intrinsic Immunity via the Inhibition of PML De Novo SUMOylation

Abstract: PML nuclear bodies (NBs) are accumulations of cellular proteins embedded in a scaffold-like structure built by SUMO-modified PML/TRIM19. PML and other NB proteins act as cellular restriction factors against human cytomegalovirus (HCMV); however, this intrinsic defense is counteracted by the immediate early protein 1 (IE1) of HCMV. IE1 directly interacts with the PML coiled-coil domain via its globular core region and disrupts NB foci by inducing a loss of PML SUMOylation. Here, we demonstrate that IE1 acts via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 61 publications
3
47
0
Order By: Relevance
“…Nevertheless, one might speculate that PML has the potential to negatively influence the activity of viral regulatory proteins by modulating their posttranslational modification status. This, however, may be abrogated by the propensity of IE1 to block PML E3 ligase functions (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, one might speculate that PML has the potential to negatively influence the activity of viral regulatory proteins by modulating their posttranslational modification status. This, however, may be abrogated by the propensity of IE1 to block PML E3 ligase functions (25).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the betaherpesvirus human cytomegalovirus (HCMV), we and others have shown that the ND10-instituted antiviral state has to be antagonized by the virus in order to efficiently start the viral gene expression program for lytic replication (reviewed in references 20 and 21). In this regard, the HCMV immediate early protein IE1p72 (IE1) plays an important role, as it is able to induce the destruction of this subnuclear structure by abrogating the SUMOylation of PML and Sp100 and it was recently shown that this is due to a blockage of de novo SUMOylation (22)(23)(24)(25). Since covalent as well as noncovalent SUMO interactions constitute the basis for ND10 formation, this ultimately leads to a loss of PML-NB integrity (26)(27)(28)(29).…”
mentioning
confidence: 99%
“…In addition to their roles in telomere stability, PML-NBs have antiviral defense functions (36), (35). In contrast to many other viruses including HSV, CMV, EBV and HHV-8, HHV-6A/B infection does not lead to the dispersal of PML-NBs but rather to PML-NBs coalescence (38), (66), (67), (68), (33). Whether this affects antiviral functions of PML-NBs remains to be determined.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, the mechanisms of action by which pp71 and IE1 antagonize silencing from the PML bodies are different: pp71 induces SUMOyilation and degradation of DAXX (26), while IE1 blocks PML SUMOylation, leading to dispersion of the PML bodies (43).…”
Section: Discussionmentioning
confidence: 99%